2007
DOI: 10.1038/ng.2007.9
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral reconstruction of segmental duplications reveals punctuated cores of human genome evolution

Abstract: Human segmental duplications are hotspots for nonallelic homologous recombination leading to genomic disorders, copy-number polymorphisms and gene and transcript innovations. The complex structure and history of these regions have precluded a global evolutionary analysis. Combining a modified A-Bruijn graph algorithm with comparative genome sequence data, we identify the origin of 4,692 ancestral duplication loci and use these to cluster 437 complex duplication blocks into 24 distinct groups. The sequence-dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
256
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(264 citation statements)
references
References 41 publications
7
256
1
Order By: Relevance
“…of CNVs in the region. 9,20,21 . A recent study reported 111 SD hotspots mediated by non-allelic homologous recombination, and the authors investigated the presence of CNVs in the hotspots 41 .…”
Section: Less Frequent Cnvs Of Genes Neighbouring Ohnologsmentioning
confidence: 99%
See 1 more Smart Citation
“…of CNVs in the region. 9,20,21 . A recent study reported 111 SD hotspots mediated by non-allelic homologous recombination, and the authors investigated the presence of CNVs in the hotspots 41 .…”
Section: Less Frequent Cnvs Of Genes Neighbouring Ohnologsmentioning
confidence: 99%
“…It has been reported that non-homologous end-joining, transposable elements 17 and DNA replication time 18,19 are also associated with CNVs. Segmental duplications (SDs) strongly correlate with CNVs 20 , and it has been proposed that SDs induce recurrent duplications through non-allelic homologous recombination resulting in the generation of CNV hotspots 9,21 .…”
mentioning
confidence: 99%
“…For example the CCL3L1 gene, which encodes a potent human immunodeficiency virus (HIV)-1-suppressive chemokine, shows striking geographical structuring among human populations, indicating that variability in copy number has probably contributed to adaptation to different environmental conditions [16]. Such geographical differences have contributed to the view that some CNVs may not only evolve in a neutral fashion, but may be also under selection [15,17,18]. In particular, those CNVs that have experienced positive selection may be of particular interest because of their beneficial role in adaptation in human populations.…”
mentioning
confidence: 99%
“…Unique genes mapping near these duplication blocks have a ten-fold higher probability of becoming duplicated than other randomly distributed regions. The NBPF/DUF1220 domains are among the few core duplicons that exist in the human genome and appear to be responsible for much of the duplicated sequences in the pericentromeric region of chromosome 1 (Jiang et al, 2007). These large, high-identity duplication blocks are prone to rearrangements that lead to the formation of both harmless and pathogenic copy number variations, as discussed in the following section.…”
Section: The Nbpf Gene Family and Human Evolutionmentioning
confidence: 99%
“…Additionally, the total absence of tandem repeats of NBPF HOR copies in chimpanzees while 47 tandem repeat HOR copies are present in human genomes reflects a human accelerated HOR pattern that distinguishes humans from nonhuman primates ( Figure 4B) (Paar et al, 2011). It has been shown that genes with an important contribution to human evolution, like the NBPF gene family, are located in human segmental duplications, which are frequently organised around core duplicons (Jiang et al, 2007). Comparison of chimpanzee and man shows that new lineage-specific segmental duplications map preferentially near shared ancestral duplications, a phenomenon called duplication shadowing (Cheng et al, 2005).…”
Section: The Nbpf Gene Family and Human Evolutionmentioning
confidence: 99%